Islamic Social Finance Innovation: Strategic Integrationof Waqf-Linked Sukuk for Sustainable Cooperative Development - Aris, Diba Anggraini; Siregar, Hermanto; Mariyanti, Tatik; Ismal, Rifki; M. Suryadinata, M. Suryadinata (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
The study aims to formulate strategies for utilizing waqf linked sukuk in cooperatives to accelerate economic recovery using the Tawhidi String Relation (TSR) approach. Qualitative descriptive approaches are use in this study with Analytical Network Process (ANP) and interview from multi stakeholders in each field, library studies as the data collection techniques. The findings of this research identify various strategies, including strengthening the professionalism of Sharia cooperatives as Nazhir; strengthening coordination between regulators; Strengthening education and literacy effectiveness; accommodate the effectiveness of the legislation; and strengthening regulations to support effectiveness. The main strategy in developing effectiveness for strengthening of sharia cooperatives to accelerate economic recovery lies in strengthening the professionalism of sharia cooperatives as nazhir, so it must be the main concern for the effectiveness development strategy. This study might only benefit Indonesian policymakers, but it may also benefit other countries which have similar character.